2014
DOI: 10.1063/1.4891042
|View full text |Cite
|
Sign up to set email alerts
|

Application of lateral photovoltage towards contactless light beam induced current measurements and its dependence on the finite beam size

Abstract: The nature of the signal due to light beam induced current (LBIC) at the remote contacts is verified as a lateral photovoltage for non-uniformly illuminated planar p-n junction devices; simulation and experimental results are presented. The limitations imposed by the ohmic contacts are successfully overcome by the introduction of capacitively coupled remote contacts, which yield similar results without any significant loss in the estimated material and device parameters. It is observed that the LBIC measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Notably, the group detected the generated ac photovoltage from Si wafer, solar cell PN‐junction, non‐uniformly ion‐implanted junction, and partly‐deep junction capacitively without using any metal electrode directly in contact with the front surface of the semiconductor wafer. Similarly, Abhale et al demonstrated remote contact OBIC (RC‐OBIC) where the contacts are at several diffusion length away from the DUT (Abhale & Rao, 2014). In particular, the group compared the device parameters, for example, photo‐carrier spreading length and characteristic length, obtained through capacitive contacts and Ohmic contacts and found that both the techniques yielded similar results.…”
Section: Microscopic Measurements Of Obicmentioning
confidence: 95%
See 1 more Smart Citation
“…Notably, the group detected the generated ac photovoltage from Si wafer, solar cell PN‐junction, non‐uniformly ion‐implanted junction, and partly‐deep junction capacitively without using any metal electrode directly in contact with the front surface of the semiconductor wafer. Similarly, Abhale et al demonstrated remote contact OBIC (RC‐OBIC) where the contacts are at several diffusion length away from the DUT (Abhale & Rao, 2014). In particular, the group compared the device parameters, for example, photo‐carrier spreading length and characteristic length, obtained through capacitive contacts and Ohmic contacts and found that both the techniques yielded similar results.…”
Section: Microscopic Measurements Of Obicmentioning
confidence: 95%
“…The screen generated laser of wavelength 500 nm, which enabled investigation of different photo-processes in different samples with a resolution of $1-2 μm. Similarly, Munakata et al (Munakata et al, 1982;Munakata & Matsubara, 1983) and Kinameri et al (Kinameri et al, 1988) (Abhale & Rao, 2014). In particular, the group compared the device parameters, for example, photo-carrier spreading length and characteristic length, obtained through capacitive contacts and Ohmic contacts and found that both the techniques yielded similar results.…”
Section: Cw Laser Based 1p Obicmentioning
confidence: 96%